Does the League Table Lie? The Development and Validation of the Perceived Performance in Team Sports Questionnaire (PPTSQ) - Gershgoren, Lael; Blatt, Asaf; Sela, Tal; Tenenbaum, Gershon (Frontiers in Psychology, 2021)
Objective performance measures are vastly used in sport psychology despite their inherent limitations (e.g., unaccounted baseline differences). Founded on the nature of group goals in team sports, we aimed at developing the Perceived Performance in Team Sports Questionnaire (PPTSQ) to capture the team members’ perception of their team’s performance. Accordingly, three dimensions were hypothesized: effort investment, skills execution, and perceived outcome. To measure these dimensions, items were generated to address the players’ perception of their team performance as a whole. Four samples of athletes were used to test the psychometric properties of the PPTSQ: Professional (n=231), collegiate (n=222), professional - retest (n=89), and mixed professional-collegiate (n=139). Exploratory and confirmatory factor analyses were used to estimate construct and content validities. These procedures revealed a better data fit to a 2-dimensional model that consists of effort investment and perceived outcome. The reliability analyses for the PPTSQ provide satisfactory evidence that the questionnaire is a reliable measure of perceived performance in team sport. Adequate internal consistency emerged for both dimensions (.75 < ω < .89). Furthermore, a high correlation was obtained for temporal stability. Concurrent validity was addressed by correlating the PPTSQ scores with the Group Environment Questionnaire, and the Team Assessment Diagnostic Instrument. Correlational analysis between the PPTSQ and an objective measure of performance was used to test its predictive validity. The correlations strongly support the concurrent and predictive validities of the PPTSQ. We conclude that our perceived performance questionnaire can address various objective measures shortcomings (e.g., considering base-rate biases) resulting in a more meaningful team performance metric. Implication of the PPTSQ for sport psychology research and applied work enhancement are discussed in details.